2008
DOI: 10.1007/s10827-008-0084-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the role of lateral membrane diffusion in AMPA receptor trafficking along a spiny dendrite

Abstract: AMPA receptor trafficking in dendritic spines is emerging as a major postsynaptic mechanism for the expression of plasticity at glutamatergic synapses. AMPA receptors within a spine are in a continuous state of flux, being exchanged with local intracellular pools via exo/endocytosis and with the surrounding dendrite via lateral membrane diffusion. This suggests that one cannot treat a single spine in isolation. Here we present a model of AMPA receptor trafficking between multiple dendritic spines distributed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…Although the young adult worms we study are approximately 96 hours old, the number of synaptic GLR-1 receptors at more distal synapses was reduced in the absence of UNC-116/KIF5-mediated transport (Figure 5E). Assuming that the diffusion constant for receptors in the cell membrane is approximately 0.1 µm 2 /s (Earnshaw and Bressloff, 2008), we estimate that 96 hours is sufficient time for GLR-1 receptors to diffuse to proximal synapses, but not long enough to reach distal synapses. In support of this, line scans of GLR-1∷GFP fluorescence in unc-116(RNAi) , and unc-116(rh24) mutants revealed dramatically reduced fluorescence in the distal processes when compared to fluorescence in more proximal regions, a pattern consistent with a diffusion-driven process (Figure S6A).…”
Section: Resultsmentioning
confidence: 99%
“…Although the young adult worms we study are approximately 96 hours old, the number of synaptic GLR-1 receptors at more distal synapses was reduced in the absence of UNC-116/KIF5-mediated transport (Figure 5E). Assuming that the diffusion constant for receptors in the cell membrane is approximately 0.1 µm 2 /s (Earnshaw and Bressloff, 2008), we estimate that 96 hours is sufficient time for GLR-1 receptors to diffuse to proximal synapses, but not long enough to reach distal synapses. In support of this, line scans of GLR-1∷GFP fluorescence in unc-116(RNAi) , and unc-116(rh24) mutants revealed dramatically reduced fluorescence in the distal processes when compared to fluorescence in more proximal regions, a pattern consistent with a diffusion-driven process (Figure S6A).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of homeostatic synaptic plasticity (HSP) mechanisms (Lissin et al 1998;O'Brien et al 1998;Turrigiano et al 1998) may coexist in dendrites together with STDP and could contribute to synaptic democracy (Earnshaw and Bressloff 2008). Because the time constant of HSP is typically much longer (hours) than that of STDP, if both mechanisms operate on the same biophysical parameter (e.g., the density of APMA receptors), we found that HSP does not counterbalance STDP (simulation results not shown).…”
Section: Other Possible Mechanisms For "Saving" Distal Synapsesmentioning
confidence: 86%
“…Let p(x, t) denote the probability density (per unit area) that a surface receptor is located within the dendritic membrane at position x at time t. Similarly, let R j (t), S j (t) denote the probability that the receptor is trapped at the surface of the jth spine or within an associated intracellular pool, respectively. A simple version of the 1D diffusion-trapping model of AMPA receptor trafficking takes the form (Bressloff and Earnshaw, 2007;Earnshaw and Bressloff, 2008) …”
Section: Diffusion Along Spiny Dendritesmentioning
confidence: 99%